2017
DOI: 10.1002/jum.14246
|View full text |Cite
|
Sign up to set email alerts
|

Exoanal Imaging of the Anal Sphincters

Abstract: Since its introduction in the early 1990s, endoanal sonography has become the mainstay of morphologic assessment of the anal canal and sphincter, especially for obstetric anal sphincter trauma. Lack of availability of suitable systems and the invasive nature of the method have limited uptake and clinical utility. More recently, exoanal or transperineal/translabial tomographic imaging has been developed as a noninvasive alternative. This pictorial overview aims to introduce the reader to this new diagnostic mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
124
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(126 citation statements)
references
References 42 publications
1
124
0
1
Order By: Relevance
“…Most obstetric units have a convex transducer and the method is non‐intrusive and therefore less bothersome for the patient. Furthermore, assessment of the pelvic floor muscles can be performed during both relaxation and contraction of the pelvic floor, and the anal mucosa as well as signs of pelvic organ prolapse can be visualized . Recently, very good repeatability in detecting OASIS with TPUS, regardless of experience, has been shown…”
Section: Introductionmentioning
confidence: 99%
“…Most obstetric units have a convex transducer and the method is non‐intrusive and therefore less bothersome for the patient. Furthermore, assessment of the pelvic floor muscles can be performed during both relaxation and contraction of the pelvic floor, and the anal mucosa as well as signs of pelvic organ prolapse can be visualized . Recently, very good repeatability in detecting OASIS with TPUS, regardless of experience, has been shown…”
Section: Introductionmentioning
confidence: 99%
“…), using proprietary software 4D View v10 (GE Healthcare), while blinded to all clinical data. Multislice, or TUI, was used to evaluate external (EAS) and internal (IAS) anal sphincter trauma in volumes obtained with the woman at rest and on PFMC, as described previously. A set of eight transverse TUI slices was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…External anal sphincter trauma was evaluated on PFMC using tomographic imaging, as previously described . A set of eight slices was obtained and the EAS was encompassed by placing one slice cranial to the EAS (at the level of the puborectalis muscle) and another caudal to the internal anal sphincter (IAS) at the level of the anal verge, with variable inter‐slice interval, depending on the length of the EAS . The remaining six slices were used to demonstrate the EAS.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining six slices were used to demonstrate the EAS. A significant EAS defect was diagnosed if at least four out of six slices showed an EAS defect of ≥ 30° of circumference . This paper focuses exclusively on EAS trauma as we have previously shown that IAS defects were less likely to be predictive of AI diagnosed using our methodology on translabial ultrasound .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation